2017
DOI: 10.17236/sat00104
|View full text |Cite
|
Sign up to set email alerts
|

Eating and rumination behaviour in cows with traumatic reticuloperitonitis

Abstract: Eating and rumination behaviour in 22 cows with traumatic reticuloperitonitis was recorded after the start of treatment. Based on the results of clinical, ultrasonographic and radiographic examinations, the cows were divided into two groups: Group A consisted of 12 cows without an intramural or perforating foreign body and group B had 10 cows with an intramural or perforating foreign body. Cows of group A received amoxicillin, flunixin meglumine and a NaCl-glucose infusion, and cows of group B received the sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 13 publications
0
9
1
2
Order By: Relevance
“…This study confirmed that cows inseminated with semen infected with BDV do not have overt clinical signs of illness [ 11 ] even with stringent health monitoring that included twice-hourly intraruminal temperature measurements and continuous recording of eating and rumination activities. The latter are sensitive criteria for the assessment of bovine wellbeing because sick cows usually have reduced rumination times, fewer regurgitated cuds and fewer chewing cycles per cud [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…This study confirmed that cows inseminated with semen infected with BDV do not have overt clinical signs of illness [ 11 ] even with stringent health monitoring that included twice-hourly intraruminal temperature measurements and continuous recording of eating and rumination activities. The latter are sensitive criteria for the assessment of bovine wellbeing because sick cows usually have reduced rumination times, fewer regurgitated cuds and fewer chewing cycles per cud [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Even though we assessed feeding time for animals of different breeds, we only included one Brown Swiss into our study, so breeds should not have influenced our results. Rumination time is a reliable indicator for the well-being of cattle (Braun et al, 2017). According to previous research, duration of rumination is 441 min per 24 h in healthy animals of different breeds with 55 chews per bolus (Braun et al, 2015c).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the clinical recommendation to wait several days after magnet administration before opting for surgical treatment or euthanasia is reasonable because attachment of a foreign body to a magnet may require a few days. Eating and rumination variables of cows with TRP were shown to normalise rapidly within 3–4 days after successful treatment with a magnet [ 31 ]. On the other hand, unnecessary delay of surgery in cattle with a perforating foreign body carries the risk of complications such as traumatic pericarditis or abscess of the liver or spleen.…”
Section: Discussionmentioning
confidence: 99%
“…This supports our earlier recommendation that the first line of treatment in cows with TRP is administration of a magnet [ 30 ] except when a large part or the entire foreign body is situated outside of the reticulum. The response to treatment is considered positive when the rectal temperature normalises and eating and rumination improve [ 31 ] but can also be confirmed radiographically. Ultrasonography is not a suitable tool for determining the short-term response to treatment because attachment of a foreign body to a magnet cannot be visualised and it takes several months for inflammatory lesions to heal [ 32 ].…”
Section: Discussionmentioning
confidence: 99%